2012
DOI: 10.1177/0961203312451201
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical significance of anti-ribosomal P antibody in childhood-onset systemic lupus erythematosus

Abstract: Anti-P is frequently observed in cSLE patients and was associated with the presence of anxiety in this cohort of cSLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 55 publications
1
23
0
1
Order By: Relevance
“…Agius et al published a case that initially presented with acute psychosis accompanied by chronic movements and of all the lab parameters only ribosomal P antibodies were positive [24]. Moreover in a study by Aldar et al on 50 pediatric SLE patients, antiribosomal P antibodies were positive in 13 patients and only one of these patients had chorea [25]. However, there is no data regarding only antiribosomal P antibodies were positive and antiphospholipid antibodies were negative in this patient.…”
Section: Discussionmentioning
confidence: 92%
“…Agius et al published a case that initially presented with acute psychosis accompanied by chronic movements and of all the lab parameters only ribosomal P antibodies were positive [24]. Moreover in a study by Aldar et al on 50 pediatric SLE patients, antiribosomal P antibodies were positive in 13 patients and only one of these patients had chorea [25]. However, there is no data regarding only antiribosomal P antibodies were positive and antiphospholipid antibodies were negative in this patient.…”
Section: Discussionmentioning
confidence: 92%
“…Since MDM2 has been demonstrated as an important negative regulator of p53 and anti-p53 was also been reported to be found in SLE patients [ 12 ], whether there was an association between anti-MDM2 and anti-p53 is still unknown. We further investigated the presence of anti-p53 in these SLE patients by ELISA.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, p53 has been found to be important in both innate and acquired immune regulation [ 20 , 21 ], and it was necessary in the inhibition of autoimmune inflammation [ 22 ]. Several studies have found that the presence of anti-p53 in SLE patient, with a prevalence of about 26%–59%, showed that anti-p53 was related to anti-DNA antibodies and can be used as a marker for detecting the disease activity of SLE [ 12 , 23 , 24 ]. Our study showed that anti-p53 was presented in 39.50% of SLE patients, and the titer of anti-p53 was positively correlated with anti-MDM2.…”
Section: Discussionmentioning
confidence: 99%
“…These antibodies can cause apoptosis by increasing the calcium influx and activation of caspase-3 27. For this study, aP-ABs were quantified using a commercial ELISA assay (QuantaLite Ribosome P assay; Kit k981237; Inova Diagnostics; San Diego, California, USA) with values of at least 20 units/mL, representing a positive result.…”
Section: Methodsmentioning
confidence: 99%